Impact of propylene- and ethylene glycol-based deicing materials on the environment and airports infrastructure - Бахтин, Анатолій Ігорович; Шкільнюк, Ірина Олександрівна; Бойченко, Сергій Валерійович (Science-based technologies, 2021)
Snow, frost and ice formations on aircraft surfaces have a negative impact on aerodynamic and operational properties of aircraft. Ethyleneglycol and propyleneglycol are the most used components of liquids for aircraft deicing that have an environmental impact. Deicing agents are toxic and pollute the environment when they enter soil or water bodies. These substances evaporate during the treatment of aircraft and in the case of ethylene glycol have an unpleasant dizzying odor that enters the air and is carried by air currents. Deicing materials can cause problems with corrosion of maintenance materials (aircraft skin, engine blades, aerodrome coating, etc.). The article analyzes a large amount of domestic and foreign technical and regulatory information, which allowed a comprehensive comparison of physicochemical and operational properties of propylene- and ethylene glycol-containing deicing materials, as well as to investigate their impact on ecosystem components, including the humans. Comparative studies show that propylene glycol is inert to living organisms and humans. Ethylene glycol adversely affects reproductive function, metabolism, immune system and reduces haemoglobin. The LD50 (total toxicity indicator) of ethylene glycol is more than 4 times lower compared to propylene glycol, which confirms the extremely high toxicity of ethylene glycol and deicing substances containing it. Propylene glycol-based deicing fluids are more environmentally friendly due to low toxicity, increased biodegradation under the same operational requirements